Desire for self-control and task performance: A plan is a key - Uziel, Liad; Price, Mindi; Alquist, Jessica L. (Frontiers in Psychology, 2022)
This research reports two studies testing whether implementation intentions can improve performance for people high in Desire for Self-Control (DSC). DSC reflects a wish to have more self-control and was previously found to be associated with impaired self-control performance. We hypothesized that implementation intentions could reverse the effect by providing clear guidance on how to handle self-control challenges. Two experiments (Ns = 175, 302) tested this hypothesis using different self-control tasks and manipulated and measured DSC. Results from both studies showed that DSC interacts with implementation intentions, such that among individuals high in DSC (but not among individuals low in DSC), implementation intentions were helpful in improving self-control performance. Implications, limitations, and future directions are discussed.